2,4,5,6-Substituted 4,5-dihydro-1,2,4,5-tetrazin-3(2H)-ones as non-classical initiators of controlled radical polymerization of styrene - Votkina D. E. Darjya Evgenjevna; Rollet M.; Trusova M. E. Marina Evgenievna; Audran G. Gerard; Marque S. R. A. Sylvain R. A.; Petunin P. V. Pavel Vasilievich; Postnikov P. S. Pavel Sergeevich (2022, 2022)
Title screen